Variation of the Level of Cytokines in Synovial Fluid of Equine with Joint Disease Treated with Bisphosphonates - Polli, Magali; Caggiano, Nicolás; Perrone, Gustavo; Marino, Mario; De Simone, Emilio; Chiappe Barbará, Angelina (Revista Complutense de Ciencias Veterinarias, 2013)
Osteoarthritis is one of the most common joint diseases in sport horses and is also cause of great economic losses associated. Early diagnosis of this disease, which sometimes is not feasible with radiographic studies, brings the possibility of early treatment in order to avoid greater commitment of underlying subchondral bone. While related cytokines play a physiological role in normal arthicular bone remodeling their increase may be considered pathological. This study postulates the determination of osteoarthicular cytokine levels (TNF-α, IL-1 β, IL-6, IL-4), as early diagnosis of osteoarthritis as well as for the evaluation of pamidronate, an aminobisphosphonates of second generation, post treatment OA evolution. We divided the animals in three groups that were classified according to the presence or not of joint disease and also considering degree of activity of OA and treatment response with bisphosphonates. As can be observed, the cytokines levels were elevated during active joint disease, and decreased after bisphosphonates treatment.
Keywords: Cytokines osteoarthicular; TNF-α; IL-1 β; IL-6; IL-4; equine osteoarthritis; sinovial fluid